(3bUGFOs - (3YfJQg Hf TOGO GdYHSjs
(3ChdgG (B:s
(3bGd RgjQ Hf CHj Sdei jeOM GdMGQK Hf Yha hgQe Hf SfGf GdeoQqHjQ hjPcQ SYjgeG HGdUdM Hjf YHS hPHjGf Cef Ce Chai OefI de Jcde HMheGfg GdOQGL hGdeJKde s
(3BNQgG (B:s
(3hcGf aJi GdgjLGA jMji ReGQgG hjVQH YfO GdcQ cd HfGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B101 s
Keywords: (3GdCOHs